The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.20945/2359-3997000000340
|View full text |Cite
|
Sign up to set email alerts
|

Galanin and glypican-4 levels depending on metabolic and cardiovascular risk factors in patients with polycystic ovary syndrome

Abstract: Objective: Galanin is a neuropeptide which has effects not only on metabolic syndrome but also on reproduction. Glypican-4 is an adipokine associated with insulin sensitivity by interacting directly with the insulin receptor. This study evaluated serum concentrations of galanin and glypican-4 in relation with the hormonal profile as well as metabolic and cardiovascular risk factors in patients with and without polycystic ovary syndrome (PCOS). Subjects and methods: A total of 44 women with PCOS and 44 age-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…17 galanin compared with controls. 18 In addition, multiple linear regression analyses revealed that PCOS and BMI seemed to be the best predictors influencing galanin levels with a decreasing and increasing effect, respectively. However, we found contradictory findings in women with infertility with PCOS in the present study, compared with the last two studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…17 galanin compared with controls. 18 In addition, multiple linear regression analyses revealed that PCOS and BMI seemed to be the best predictors influencing galanin levels with a decreasing and increasing effect, respectively. However, we found contradictory findings in women with infertility with PCOS in the present study, compared with the last two studies.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, Bidzińska‐Speichert et al noted that patients with PCOS had reduced galanin concentrations compared with controls 17 . Altınkaya et al claimed that women with PCOS possessed decreased serum levels of galanin compared with controls 18 . In addition, multiple linear regression analyses revealed that PCOS and BMI seemed to be the best predictors influencing galanin levels with a decreasing and increasing effect, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This increase correlated positively with testosterone and LH levels and negatively with estradiol (E2). It is thought that increased phoenixin-14 expression in PCOS patients is associated with up-regulation of LH and androgen production [ 64 ].…”
Section: Other Neurohormones and Adipokines In Pcos (Phoenixin-14 Gal...mentioning
confidence: 99%
“…Furthermore, serum TNF-a and IL-6 levels were significantly increased in PCOS group, which was reversed with galanin treatment (29). Altinkaya compared serum galanin levels in 44 women with PCOS and 44 age-matched controls and found that women with PCOS were characterized by lower galanin levels than controls (30), indicating that supplementation of galanin may be a new therapeutic approach for PCOS, which still needs more evidence to support.…”
Section: Galaninmentioning
confidence: 99%